Keunggulan Kompetitif Investasi Emas Syariah Pegadaian Syariah Cabang Blauran - Siska Dwi Oktavia; Sirajul Arifin (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study analyzes the competitive advantage of sharia gold investment at Pegadaian Syariah, Blauran Branch, Surabaya, amidst competition from Bank Syariah Indonesia and sharia fintech. Using a descriptive qualitative approach, primary data was obtained through semi-structured interviews with Branch Managers, marketing staff, and customers, while secondary data came from Pegadaian reports, OJK publications, and the World Gold Council. The analysis employed the SWOT framework and Porter's Five Forces. The results show that Pegadaian Syariah's competitive advantage stems from public trust in its state-owned enterprise (BUMN) status, compliance with sharia principles, certified Galeri24 products, and product flexibility starting from IDR 10,000 supported by the PSDS digital platform. There is a significant opportunity from the 135% year-on-year surge in gold demand, but it faces the threat of intense competition and high buyer bargaining power. Competitive advantage strategies are implemented through digital service differentiation, an inclusive market focus, and cost efficiency. The study recommends intensifying PSDS education, strengthening gold investment literacy, and optimizing pricing to increase competitiveness.